PENYELESAIAN SENGKETATRANSAKSI JUAL BELI MELAUI INTERNET (E-COMMERCE) - Darmawan Tri Budi Utomo (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2010)
Buying and selling transaction through internet makes people everywhere and at any time easy to make buying and selling agreement without face-to-face encounter. By electronic buying and selling transaction, people can buy and sell effectively and efficiently everywhere and at any time. In transacting, people keep referring to the existing legal norms. In buying and selling transaction through internet, various legal problems that can inflict a loss upon the other parties will appear. By the existence of the Law No. 11/2008 on Information and Electronic Transaction, it is hoped that the emerging dispute among the parties in the buying and selling transaction through internet can be settled.